Pain in pancreatitis: issue and ways out - A. V. Okhlobystin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. To present the modern data on pain sensitivity at pancreatic lesion, interrelation of mechanisms of inflammation and nociception, to determine main directions in pain relief at chronic pancreatitis (CP), to demonstrate potentials of modern enzyme preparations for this purpose.Original points. Chronic pancreatitis is characterized by resistant pain in comparison to other gastroenterological diseases. Abdominal pain determines quality of life of CP patient to the highest degree of all other symptoms. It can be related to intraductal hypertension caused both by pancreatic juice outflow obstruction, and by increased volume as a result of activated stimulation. Intrapancreatic parenchymal pressure is increased exceeding perfusion pressure of pancreatic capillaries that causes ischemia. At CP there is sensitization to pain. Histological study frequently reveals signs of neural damage, inflammatory mediators often can act as pain mediators. Sensitization affect not only nerve terminals, but neurones of spinal cord and brain as well. Patients develop plastic changes in central nervous system as well, i.e. «remodeling», enhancing pain perception. This may cause pain persistance after block of peripheral nociceptive pathways or after total pancreatectomy («pancreatic pain in the without the pancreas»). The CP diagnosis should be based on revealing of irreversible changes of the pancreas by modern radiological diagnostic methods: pancreatic enlargement 1,5 times and more, dilation, presence of strictures or severe irregularity of main pancreatic duct, calcification or parenchymal atrophy. It is also important to detect prominent ductal changes (strictures, stones), requiring endoscopic or surgical treatment as promptly as possible. Medical treatment of pain includes, first of all, elimination of toxic factors and stimulations of pancreatic secretion. Smoking cessation is important no less. Pancreatic enzymes represents the basis of pharmaceutical treatment nowadays. Their application is based on multiple negative feedback mechanisms involved in pancreatic secretion regulation. The high contents of proteases in the drug «Ermital» allows to relieve pain effectively, reduce number of taken capsules per day. Absence of phthalates, which can be dangerous at pregnancy, in microtablets coating is major advantage. Besides enzymes, antisecretory drugs represent another integral component of CP patients treatment. Many patients require prescription of analgetics. Tramadol and propoxyphene to acetaminophen combination are used most often. Development of TRPV4 and TRPA1A ionic channels blockers is perspective direction in pancreatic pain relief.Conclusion. Drug therapy of pancreatic pain is based on digestive enzymes, antisecretory and analgetic agents.